E-Learning Education a Potential Learning Solution for Rural India - Kiran Haresh Varekar (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Mobile phones, internet, tablets, IPads, their applications, social media etc are part of our lives from the start till the end of the day. Technology is touching every aspect of society and changing it drastically. But there is one very important part of the society that has also been touched by new innovations and discoveries with its golden hands and that is education with the concept of E-learning. Like all other areas, in this case also urban areas are influenced to a greater extent than rural areas. So much more could have been done to bring the revolution in learning process in rural areas of India. In this research paper development through E-learning and its barriers with future solution in rural India is observed. In this research paper, we observed that E-learning is an effective tool for development of educational sector in India. E-learning is learning, utilizing electronic technologies to access educational curriculum outside of a traditional classroom. In most cases, it refers to a course, program or degree delivered completely online. The basic objective of this research paper is to understand concept of e-learning with its challenges and solution to examine the type of e-learning. The research paper focused on e-learning in rural India.